Quality of Life and Burden of Moderate-to-Severe Atopic Dermatitis in Adult Patients Within the Asia-Pacific Region: A Cross-sectional Survey - Chia-Yu Chu; Yung Chan; Siriwan Wananukul; Hao Cheng; Nisha Suyien Chandran; Ramesh Bhat; Sang Wook Son; Han-Fang Liao; Sean Gardiner; Qi Qing Ng; See-Hwee Yeo; Sophie Bozhi Chen; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction The burden of atopic dermatitis (AD) is significant, with a substantial impact on quality of life (QoL). This cross-sectional study aimed to ascertain the burden of AD, its impact on QoL, and associated costs. Methods Patients with moderate-to-severe AD were enrolled from eight territories, namely Hong Kong, India, Japan, Mainland China, Singapore, South Korea, Taiwan, and Thailand. After screening was performed and informed consent was obtained, eligible participants were asked to provide responses on their AD symptoms, severity, treatment, and out-of-pocket costs via an online survey. QoL was assessed using EQ-5D-5L and Dermatology Life Quality Index (DLQI), while productivity loss was quantified using the Work Productivity and Activity Impairment (WPAI) questionnaire. Data from completed submissions were analyzed using descriptive statistics. The study was reviewed by the institutional review board in each territory. Results Median age of enrolled patients (N = 1103) was 41.0 years (interquartile range, IQR 16.0). The majority of patients reported that their head/neck, trunk, upper limbs, and lower limbs were affected during a flare. Topical (74.2%) and oral steroids (58.7%) were frequently prescribed to manage AD. Common atopic comorbidities were allergic urticaria (64.2%), allergic rhinitis (61.8%), and allergic conjunctivitis (51.5%). Median DLQI score was 13.0 (IQR 11.0), while median EQ-5D-5L (based on China value set) score was 0.8 (IQR 0.4); 87.2% and 77.2% of patients reported pain/discomfort and anxiety/depression on the EQ-5D-5L domains, respectively. Median total annual costs associated with AD were USD 10,128.52 (IQR 12,963.26) per patient, with indirect costs being the largest component. Findings from WPAI indicated that presenteeism is a major contributor to productivity loss. Conclusion This multinational survey study showed that AD is associated with substantial QoL impairment and economic burden among Asian adult patients with moderate-to-severe AD. To alleviate burden of AD, clinicians should be more proactive in managing other concomitant conditions including psychological issues, and advocate for increased reimbursement for AD treatments.